Microbial conversion of glycerol to 1,3-propanediol$ephysiological comparison of a natural producer, Clostridium butyricum VPI 3266, and an engineered strain, Clostridium acetobutylicum DG1 (pSPD5) - González-Pajuelo, María (2011)
Clostridium acetobutylicum is not able to grow on glycerol as the sole carbon source since it cannot reoxidize the excess of NADH generated by glycerol catabolism. Nevertheless, when the pSPD5 plasmid, carrying the NADH-consuming 1,3-propanediol pathway from C. butyricum VPI 3266, was introduced into C. acetobutylicum DG1, growth on glycerol was achieved, and 1,3-propanediol was produced. In order to compare the physiological behavior of the recombinant C. acetobutylicum DG1(pSPD5) strain with that of the natural 1,3- propanediol producer C. butyricum VPI 3266, both strains were grown in chemostat cultures with glycerol as the sole carbon source. The same “global behavior” was observed for both strains: 1,3-propanediol was the main fermentation product, and the qH2 flux was very low. However, when looking at key intracellular enzyme levels, significant differences were observed. Firstly, the pathway for glycerol oxidation was different: C. butyricum uses a glycerol dehydrogenase and a dihydroxyacetone kinase, while C. acetobutylicum uses a glycerol kinase and a glycerol-3-phosphate dehydrogenase. Secondly, the electron flow is differentially regulated: (i) in C. butyricum VPI 3266, the in vitro hydrogenase activity is 10-fold lower than that in C. acetobutylicum DG1(pSPD5), and (ii) while the ferredoxin-NAD reductase activity is high and the NADH-ferredoxin reductase activity is low in C. acetobutylicum DG1(pSPD5), the reverse is observed for C. butyricum VPI 3266. Thirdly, lactate dehydrogenase activity is only detected in the C. acetobutylicum DG1(pSPD5) culture, explaining why this microorganism produces lactate.